A Photoaffinity Displacement Assay and Probes to Study the Cyclin‐Dependent Kinase Family. (31st October 2019) - Grant, Emma K.; Fallon, David J.; Eberl, H. Christian; Fantom, Ken G. M.; Zappacosta, Francesca; Messenger, Cassie; Tomkinson, Nicholas C. O.; Bush, Jacob T.
Abstract: The CDK family plays a crucial role in the control of the cell cycle. Dysregulation and mutation of the CDKs has been implicated in cancer and the CDKs have been investigated extensively as potential therapeutic targets. Selective inhibition of specific isoforms of the CDKs is crucial to achieve therapeutic effect while minimising toxicity. We present a group of photoaffinity probes designed to bind to the family of CDKs. The site of crosslinking of the optimised probe, as well as its ability to enrich members of the CDK family from cell lysates, was investigated. In a proof of concept study, we subsequently developed a photoaffinity probe‐based competition assay to profile CDK inhibitors. We anticipate that this approach will be widely applicable to the study of small molecule binding to protein families of interest. Abstract : Momentaufnahmen mit PALs : Photoaffinitätssonden wurden entworfen, die auf cyclinabhängige Kinasen (CDKs) abzielen und CDKs aus Zelllysaten kompetitiv anreichern. Ein biochemischer Photoaffinitätsverdrängungsassay wurde ebenfalls entwickelt, um die Wirkstärken der Verbindungen zu messen.